CORRELATION OF RUPIAH EXCHANGE RATE, INTEREST RATE, AND PROFITABILITY RATIO TO BETA ISLAMIC STOCK - Chomsi Hariati; Nur Suci IMM (Universitas Hayam Wuruk Perbanas, 2013)
This study discusses about the variables that affect the stock beta, where beta stock is systematicrisk in stocks. This study used a quantitative design with descriptive test, normality,multiple linear regressions. The sample uses the Jakarta Islamic Index at the IndonesianStock Exchange. Results of whose team it is based on the F test variable exchange rate, interestrate elbow, and profitability ratios significantly influence beta Islamic stocks. The resultsof the t test result that variable exchange rate and interest rates do not significantly influencebeta Islamic stocks, but the variable return on assets and return on investment significantlyinfluence beta Islamic stocks. Limitation of this study is that the study period was only 2years old, 28 in total sample of firms as well as fundamental and macro variables are used.